2009
DOI: 10.1186/1471-2334-9-166
|View full text |Cite
|
Sign up to set email alerts
|

Initial psychological responses to Influenza A, H1N1 ("Swine flu")

Abstract: BackgroundThe outbreak of the pandemic flu, Influenza A H1N1 (Swine Flu) in early 2009, provided a major challenge to health services around the world. Previous pandemics have led to stockpiling of goods, the victimisation of particular population groups, and the cancellation of travel and the boycotting of particular foods (e.g. pork). We examined initial behavioural and attitudinal responses towards Influenza A, H1N1 ("Swine flu") in the six days following the WHO pandemic alert level 5, and regional differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
137
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(159 citation statements)
references
References 17 publications
(21 reference statements)
11
137
2
6
Order By: Relevance
“…Several studies have investigated public perceptions about the Influenza Pandemic H1N1/09 (Goodwin et al, 2009;Lau et al, 2009;Dhand et al, 2011;Lau et al, 2011); however, limited information is available on pig producers' perceptions and experiences (Goodwin et al, 2011). This cross-sectional observational study was conducted at the height of the outbreak in the human population in Australia and before the virus was reported for the first time in an Australian piggery in July 2009 (OIE, 2009b;Holyoake et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have investigated public perceptions about the Influenza Pandemic H1N1/09 (Goodwin et al, 2009;Lau et al, 2009;Dhand et al, 2011;Lau et al, 2011); however, limited information is available on pig producers' perceptions and experiences (Goodwin et al, 2011). This cross-sectional observational study was conducted at the height of the outbreak in the human population in Australia and before the virus was reported for the first time in an Australian piggery in July 2009 (OIE, 2009b;Holyoake et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these elevated risk perceptions of the general public, a study on public perceptions of H1N1/09 in Hong Kong, reported 7% of respondents believed that eating well-cooked pork posed a risk of transmission of the virus. These public misperceptions had a negative impact on pork consumption, with a reduced consumption reported by 6% to 11% of different survey respondents (APL, 2009;Goodwin et al, 2009;Dhand et al, 2011). Despite this, a very low proportion of pig producers stated a decreased number of pigs sold during the H1N1/09 outbreak in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outbreak of the Influenza A/H1N1 (“swine flu”) in April 2009 provided a major challenge to health services around the world 16 . On account of this, the health care system needs to be aware of the safety of their HCWs because they are at significant risk of getting infected and also of transmitting the disease to patients 15 .…”
Section: Discussionmentioning
confidence: 99%